Comparative analyses of transcriptional responses of Dectes texanus LeConte (Coleoptera: Cerambycidae) larvae fed on three different host plants and artificial diet - Aguirre-Rojas, Lina M.; Scully, Erin D.; Trick, Harold N.; Zhu, Kun Yan; Smith, C. Michael (Scientific reports, 2021)
Dectes texanus is an important coleopteran pest of soybeans and cultivated sunflowers in the Midwestern United States that causes yield losses by girdling stems of their host plants. Although sunflower and giant ragweed are primary hosts of D. texanus , they began colonizing soybeans approximately 50 years ago and no reliable management method has been established to prevent or reduce losses by this pest. To identify genes putatively involved when feeding soybean, we compared gene expression of D. texanus third-instar larvae fed soybean to those fed sunflower, giant ragweed, or artificial diet. Dectes texanus larvae differentially expressed 514 unigenes when fed on soybean compared to those fed the other diet treatments. Enrichment analyses of gene ontology terms from up-regulated unigenes in soybean-fed larvae compared to those fed both primary hosts highlighted unigenes involved in oxidoreductase and polygalacturonase activities. Cytochrome P450s, carboxylesterases, major facilitator superfamily transporters, lipocalins, apolipoproteins, glycoside hydrolases 1 and 28, and lytic monooxygenases were among the most commonly up-regulated unigenes in soybean-fed larvae compared to those fed their primary hosts. These results suggest that D. texanus larvae differentially expressed unigenes involved in biotransformation of allelochemicals, digestion of plant cell walls and transport of small solutes and lipids when feeding in soybean.